Londoño & Frenk’s Structured Pluralism Regarding the Articulation and Modulation of the General System of Social Security in Health (SGSSS) in Colombia - Gutiérrez Ossa, Jahir Alexander; Restrepo Avendaño, Rubén Dario (Sociedad y Economía, 2012)
The purpose of this analytical article is to demonstrate the importance of structured pluralism -model suggested by Londoño and Frenk (1997)- for the case of Colombia. The debates on health systems have played a comparative role for the most part, offering few grounds to promote actions aimed at overcoming the structural problems of health systems in terms of finances and service provision. The methodology consisted on an exploratory and descriptive method in agreement with the proposals by the authors of the model, in order to demonstrate the fundamental role of articulation and modulation in any health system.